Patrones de excreción de aminoácidos urinarios en niños excepcionales y pacientes con trastornos mentales en Costa Rica - Céspedes, Carlos de (1983)
The amino acid profile was studied in individual random samples of urine from 1147 normal schoolchildren and 1074 exceptional children: 628 with mental retardation, 332 with hearing and speech defects and 114 with visual defects as well as in 673 patients with mental disorders. Laboratory procedures included chemical tests and one-dimension paper- electro- and column-chromatography. Phenylketonuria was found in a mentally retarded girl and in one and in one of her brothers: iminoglycinuria in a mentally retarded boy and heterozygole cystinuria in a man with manic-depressive psychosis. The percentage of high excretors of beta-aminoisobutiric acid (B-AIB) in the controls (4.88%) was similar to previous findings in the Caucasian race. The children with hearing and speech defects showed a number of high excretors of B-AIB significantly lower (X2 = 5.32; p < 0.025) and the children with visual defects a number of hyperglycinurias significantly higher (X2 = 9,19; p <0.05). Previous non-consistent findings on the excess of high excretors of B-AIB in Down’s syndrome were not confirmed in this study. These results suggest a relationship between transport defects in the plasma membrane and pathological dirsorders in some of the cases screened.